2011
DOI: 10.5056/jnm.2011.17.3.274
|View full text |Cite
|
Sign up to set email alerts
|

Gastroesophageal Reflux Disease in Type II Diabetes Mellitus With or Without Peripheral Neuropathy

Abstract: Background/AimsPatients with type II diabetes mellitus (DM) were known to have higher prevalence of gastroesophageal reflux disease (GERD). Recent studies have shown that neuropathy has positive role on the development of GERD in type II DM, although its pathogenesis has not been fully understood yet. The aim of this study was to investigate whether neuropathy really contribute to the development of GERD and typical GERD symptoms in patients with type II DM in Korea.MethodsOne hundred and nineteen patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
33
1
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 25 publications
7
33
1
3
Order By: Relevance
“…[32][33][34] It was also reported that diabetic patients with neuropathy had more gastrointestinal symptoms than those without neuropathy. 35 The present study demonstrated that STZ injection led to colonic hypersensitivity in rats in addition to peripheral sensorimotor neuropathy 36,37 and gastric hypersensitivity. 18 This is in agreement with previous reports that diabetic rats display visceral hypersensitivity.…”
Section: Discussionmentioning
confidence: 89%
“…[32][33][34] It was also reported that diabetic patients with neuropathy had more gastrointestinal symptoms than those without neuropathy. 35 The present study demonstrated that STZ injection led to colonic hypersensitivity in rats in addition to peripheral sensorimotor neuropathy 36,37 and gastric hypersensitivity. 18 This is in agreement with previous reports that diabetic rats display visceral hypersensitivity.…”
Section: Discussionmentioning
confidence: 89%
“…13,20 Still, prevalence of the disease in our study was higher than that of other similar questionnaire studies in Japan (23-29%) 16,18 and Korea (23.1%). 19 Our result even topped prevalence in Spain (28%) which also used ambulatory 24-hour esophageal pH-monitoring, 17 so that its result should have been higher consequently due to inclusion of asymptomatic GERD in DM patients.…”
Section: Discussionmentioning
confidence: 98%
“…4,[12][13][14][15] Studies conducted in various countries have shown that GERD was a frequent complication in approximately 23-29% of DM patients and reached up to half of total diabetes cases in New Jersey, United States. [15][16][17][18][19][20] Another complexity of DM in the case of GERD is that DM will give poor prognostic effect to the latter since: (1) DM will reduce the effectiveness of acid-suppression therapy, which is the mainstay therapy of GERD 21 and; (2) DM increases the occurrence of Barrett's esophagus and esophageal cancer. 22 The presence of GERD in DM patients is often missed.…”
mentioning
confidence: 99%
“…При цьому акцент робиться на дослідженні впливу діабе-тичної автономної нейропатії на ураження внутрішніх органів, зокрема органів травлення (Lee S.D., Keum B., Chun H.J., Bak Y.T.) [9].…”
Section: обговоренняunclassified